1995
DOI: 10.1152/physrev.1995.75.4.749
|View full text |Cite
|
Sign up to set email alerts
|

Human surfactant protein B: structure, function, regulation, and genetic disease

Abstract: Elucidation of the structure and function of the hydrophobic surfactant protein (SP-B) and the SP-B gene has provided critical insight into surfactant homeostasis and control of respiratory epithelial cell gene expression. Surfactant protein B, in concert with surfactant protein A (SP-A), surfactant protein C (SP-C), and surfactant phospholipids, contributes to the structure and function of surfactant particles, determining surface activities and pathways by which surfactant phospholipids and proteins are proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
96
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(98 citation statements)
references
References 0 publications
1
96
0
1
Order By: Relevance
“…In mice it has been demonstrated that only the animals homozygous for this allele were affected [40]. Interestingly, to date, six different mutations in this gene were identified [345]. The SP-B deficiency is associated with SP-A and SP-C abnormalities.…”
Section: Disorders Of Surfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice it has been demonstrated that only the animals homozygous for this allele were affected [40]. Interestingly, to date, six different mutations in this gene were identified [345]. The SP-B deficiency is associated with SP-A and SP-C abnormalities.…”
Section: Disorders Of Surfactantmentioning
confidence: 99%
“…The results of the treatment of infants suffering from this disease are still very poor. Up to now, total cardiopulmonary support, involving extracorporeal membrane oxygenation, repeated surfactant instillations, and corticosteroid therapy has not led to successful treatment [114,345].…”
Section: Disorders Of Surfactantmentioning
confidence: 99%
“…4). Homozygous mutations leading to the complete absence of SP-B in newborn human infants result in the rapid onset of respiratory distress syndrome which is refractory to mechanical ventilation and surfactant replacement (5,6).…”
mentioning
confidence: 99%
“…SP-C is the smallest (4.2-8 kDa) and the most hydrophobic surfactant protein (with 70 % of hydrophobic amino acids), and is only found in the lungs (Glasser et al, 2001). SP-B is an 8.7-kDa-protein component of tubular myelin, and enhances adsorption and re-spreading (Whitsett et al, 1995;Oviedo et al, 2001). SP-B is required for normal lung function (Melton et al, 2003;Nesslein et al, 2005).…”
mentioning
confidence: 99%